A Method for Finding the Maximal Set in Excess Demand - Tommy Andersson; Albin Erlanson; Jens Gudmundsson; Helga Habis; Jim Ingebretsen Carlson; Jörgen Kratz (Lund University, School of Economics and Management, Department of Economics, 2014)
We present a polynomial time method for identifying the maximal set in excess demand at a given payoff vector. This set can be used in "large" partnership formation problems to identify the minimum element in the set of individually rational payoff vectors at which there is no overdemanded set of agents. This minimum element corresponds to the minimum Walrasian equilibrium price vector in a special case of the partnership formation problem.
Keywords: C61; C62; 330; Partnership formation; polynomial time method; excess demand